Delineating the psychiatric and behavioral phenotype of recurrent 2q13 deletions and duplications. Issue 4 (31st March 2018) - Wolfe, Kate; McQuillin, Andrew; Alesi, Viola; Boudry Labis, Elise; Cutajar, Peter; Dallapiccola, Bruno; Dentici, Maria Lisa; Dieux‐Coeslier, Anne; Duban‐Bedu, Benedicte; Duelund Hjortshøj, Tina; Goel, Himanshu; Loddo, Sara; et al.
Abstract : Recurrent deletions and duplications at the 2q13 locus have been associated with developmental delay (DD) and dysmorphisms. We aimed to undertake detailed clinical characterization of individuals with 2q13 copy number variations (CNVs), with a focus on behavioral and psychiatric phenotypes. Participants were recruited via the Unique chromosomal disorder support group, U.K. National Health Service Regional Genetics Centres, and the DatabasE of genomiC varIation and Phenotype in Humans using Ensembl Resources (DECIPHER) database. A review of published 2q13 patient case reports was undertaken to enable combined phenotypic analysis. We present a new case series of 2q13 CNV carriers (21 deletion, 4 duplication) and the largest ever combined analysis with data from published studies, making a total of 54 deletion and 23 duplication carriers. DD/intellectual disabilities was identified in the majority of carriers (79% deletion, 70% duplication), although in the new cases 52% had an IQ in the borderline or normal range. Despite the median age of the new cases being only 9 years, 64% had a clinical psychiatric diagnosis. Combined analysis found attention deficit hyperactivity disorder (ADHD) to be the most frequent diagnosis (48% deletion, 60% duplication), followed by autism spectrum disorders (33% deletion, 17% duplication). Aggressive (33%) and self‐injurious behaviors (33%) were also identified in the new cases. CNVs at 2q13 are typically associated with DD with mildly impaired intelligence, and a high rate of childhood psychiatric diagnoses—particularly ADHD. We have further characterized the clinical phenotype related to imbalances of the 2q13 region and identified it as a region of interest for the neurobiological investigation of ADHD.